Biomass enhancement and activation of transcriptional regulation in sorghum seedling by plasma-activated water - Beak, Hong Kwan; Priatama, Ryza A.; Han, Sang-Ik; Song, Ilchan; Park, Soon Ju; Lee, Young Koung (Frontiers in Plant Science, 2024)
Introduction: Recent advancements in agricultural technology have highlighted the potential of eco-friendly innovations, such as plasma-activated water (PAW), for enhancing seed germination, growth, and biomass production. Methods: In this study, we investigated the effects of PAW irrigation on young sorghum seedlings through phenotypic and transcriptional analyses. We measured growth parameters, including seedling height, stem thickness, and biomass, across five sorghum varieties: BTx623, Sodamchal, Noeulchal, Baremae, and Hichal. Additionally, we performed detailed analyses of stem cross-sections to evaluate the structural changes induced by PAW. Whole transcriptome analysis was conducted to identify differentially expressed genes (DEGs) and to perform Gene Ontology (GO) analysis. Results: Phenotypic analysis revealed significant growth enhancements in PAW-treated seedlings compared to the control group, with notable increases in seedling height, stem thickness, and biomass. Stem cross-section analysis confirmed that PAW treatment led to the enlargement of primordia tissue, leaf sheath (LS1 and LS2), and overall stem tissue area. Transcriptomic analysis revealed that 78% of the DEGs were upregulated in response to PAW, indicating that PAW acts as a positive regulator of gene expression. Gene Ontology (GO) analysis further showed that PAW treatment predominantly upregulated genes associated with transmembrane transport, response to light stimulus, oxidoreductase activity, and transcriptional regulation. Additionally, an enriched AP2/EREBP transcription binding motif was identified.